The Insulin-Sensitizer Pioglitazone Remodels Adipose Tissue Phospholipids in Humans - Palavicini, Juan P.; Chavez-Velazquez, Alberto; Fourcaudot, Marcel; Tripathy, Devjit; Pan, Meixia; Norton, Luke; DeFronzo, Ralph A.; Shannon, Christopher E. (Frontiers in Physiology, 2021)
The insulin-sensitizer pioglitazone exerts its cardiometabolic benefits in type 2 diabetes through a redistribution of body fat, from ectopic and visceral areas to subcutaneous adipose depots. Whereas excessive weight gain and lipid storage in obesity promotes insulin resistance and chronic inflammation, the expansion of subcutaneous adipose by pioglitazone is associated with a reversal of these immunometabolic deficits. The precise events driving this beneficial remodeling of adipose tissue with pioglitazone remain unclear and whether insulin-sensitizers alter the lipidomic composition of human adipose has not previously been investigated. Using shotgun lipidomics, we explored the molecular lipid responses in subcutaneous adipose tissue following six months of pioglitazone treatment (45 mg / day) in obese humans with type 2 diabetes. Despite an expected increase in body weight following pioglitazone treatment, no robust effects were observed on the composition of storage lipids (i.e. triglycerides) or the content of lipotoxic lipid species (e.g. ceramides, diacylglycerides) in adipose tissue. Instead, pioglitazone caused a selective remodeling of the glycerophospholipid pool, characterized by a decrease in lipids enriched for arachidonic acid such as plasmenylethanolamines and phosphatidylinositols. This contributed to a greater overall saturation and shortened chain length of fatty acyl groups within cell membrane lipids, changes that are consistent with the purported induction of adipogenesis by pioglitazone. The mechanism through which pioglitazone lowered adipose tissue arachidonic acid, a major modulator of inflammatory pathways, did not involve alterations in phospholipase gene expression but was associated with a reduction in its precursor linoleic acid, an effect that was also observed in skeletal muscle samples from the same subjects. These findings offer important insights into the biological mechanisms through which pioglitazone protects the immunometabolic health of adipocytes in the face of increased lipid storage.